Sea glass cottage ebook - Hannon, Irene (Hope Harbor, 2022)
Christi Reece arrived in Hope Harbor reeling from a series of setbacks and desperate for help. But Jack Colby wants nothing to do with the woman who betrayed him—until a turn of events finds him needing her help.